Research on the Theory of Optical Transmission for Bragg Fiber With High-Index-Core - Liu, Daojun; Zhang, Ji (Frontiers in Physics, 2020)
The paper analyzes the two theories of conducted light signal for Bragg Fiber with High-index-core, namely total internal reflection and photonic band-Gap. From the perspective of the wave equation, the distribution of the electromagnetic field and the conditions for forming the guided mode when the optical signal is transmitted in the core of fiber are explained. The analysis of photonic band-Gap adopts the band structure principle of natural crystals for analogy. Then, the formation process of photonic band-Gap is elaborated on. Finally, the influence of four structural parameters of Bragg Fiber with High-index-core on fiber mode is simulated based on finite difference time domain, laying the theoretical foundation for the development of the functional devices of Bragg fiber